Survey of Bedside Clinical Neurologic Assessments in U.S. PICUs*. Issue 4 (April 2018) - Kirschen, Matthew P.; Snyder, Megan; Winters, Madeline; Ichord, Rebecca; Berg, Robert A.; Nadkarni, Vinay; Topjian, Alexis
Abstract : Objective: To understand how routine bedside clinical neurologic assessments are performed in U.S. PICUs. Design: Electronic survey. Setting: Academic PICUs throughout the United States. Subjects: Faculty representatives from PICUs throughout the United States. Interventions: None. Measurements and Main Results: We surveyed how routine bedside neurologic assessments are reported to be performed in U.S. PICUs and the attitudes of respondents on the utility of these assessments. The survey contained questions regarding 1) components of neurologic assessments; 2) frequency of neurologic assessments; 3) documentation and communication of changes in neurologic assessment; and 4) optimization of neurologic assessments. Surveys were received from 64 of 67 institutions (96%). Glasgow Coma Scale and pupillary reflex were the most commonly reported assessments (80% and 92% of institutions, respectively). For patients with acute brain injury, 95% of institutions performed neurologic assessments hourly although assessment frequency was more variable for patients at low risk of developing brain injury and those at high risk for brain injury, but without overt injury. In 73% of institutions, any change detected on routine neuroassessment was communicated to providers, whereas in 27%, communication depended on the severity or degree of neurologic decline. Seventy percent of respondents thought that their current practice for assessing and monitoring neurologic status was suboptimal. Only 57% felt that the Glasgow Coma Scale was a valuable tool for the serial assessment of neurologic function in the ICU. Ninety-two percent felt that a standardized approach to assessing and documenting preillness neurologic function would be valuable. Conclusions: Routine neurologic assessments are reported to be conducted in nearly all academic PICUs in the United States with fellowship training programs although the content, frequency, and triggers for communication vary between institutions. Most physicians felt that the current paradigms for neurologic assessments are suboptimal. These data suggest that optimizing and standardizing routine bedside nursing neurologic assessments may be warranted. Abstract : Supplemental Digital Content is available in the text.